2017
DOI: 10.1371/journal.pone.0171575
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation among patients under investigation for suspected obstructive sleep apnea

Abstract: Study objectivesObstructive sleep apnea is common among patients with atrial fibrillation, but the prevalence and risk factors for atrial fibrillation among patients who are being investigated on suspicion of sleep apnea are not well known. The aim of the study was to estimate the prevalence of atrial fibrillation among patients investigated for suspected obstructive sleep apnea and to identify risk factors for atrial fibrillation among them.MethodsThe prevalence of atrial fibrillation was investigated among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Previous studies showed that DM, severity of OSAS, lower sleep efficiency, and heart failure were significantly associated with the incidence of AF in patients with OSAS [7,10,24]. This study confirmed previous findings that DM, lower sleep efficiency, and lower LVEF were independent predictors of AF occurrence in patients with OSAS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed that DM, severity of OSAS, lower sleep efficiency, and heart failure were significantly associated with the incidence of AF in patients with OSAS [7,10,24]. This study confirmed previous findings that DM, lower sleep efficiency, and lower LVEF were independent predictors of AF occurrence in patients with OSAS.…”
Section: Discussionsupporting
confidence: 90%
“…There is a growing body of evidence suggesting that OSAS is considered a risk factor for AF [7]. The incidence of AF in OSAS patients varies from 7.6% to 20% in different studies investigating different populations and using different detection methods [7,9,10]. There are some reports on the relationship between AF and OSAS that show the incidence of AF is associated with OSAS severity, that AF patients with OSAS have a worse prognosis (a higher AF recurrence rate) whether receiving medication or ablation therapy [6,7] and that the treatment strategy (e.g., nasal continuous positive airway pressure) for OSAS may decrease the number of AF attacks [11].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AF is reported to be approximately 7.6% in patients with suspected OSA, and it increases with the severity of OSA [16] . However, the prevalence in elderly patients with OSA has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Screening is especially necessary for populations with an underlying risk factor for stroke or systemic embolism, such as hypertension, diabetes mellitus (Kishimoto et al, 2016), or sleep apnea (Hendrikx et al, 2017). The ESC guidelines recommend AF screening in accordance with the CHA 2 DS 2 -VASc score (Kirchhof et al, 2016).…”
Section: Wristwatch-based Pwmmentioning
confidence: 99%